RENDEMEN DAN KARAKTERISTIK MINYAK KAYU PUTIH PADA UKURAN DAUN YANG BERBEDA - Nengsih, Yurdia; Tri Ratnaningsih, Ambar; Suhesti, Eni (Fakultas Kehutanan Universitas Lancang Kuning, 2019)
This research was conducted in the presumptuous university forest faculty laboratory yellow Pekanbaru. This research was conducted for 6 months, namely from July -December 2018. This study aims to measure the yield and characteristics eucalyptus oil at various leaf sizes consisting of specific gravity, refractive index, solubility in 70% alcohol, and cineol content. Analyze effect size eucalyptus leaves to the characteristics of eucalyptus oil. This research is using a completely randomized design (CRD). This research is used to obtain provide information and input regarding the characteristics of eucalyptus oil and yield at different leaf sizes. Results from research on oil characteristics Eucalyptus at various leaf sizes consists of, whole eucalyptus leaves obtained yield 0.59%, moisture content 1.074%, specific gravity 0.953, refractive index 1.467, solubility in 70% 1: 2 alcohol, the cineol content is 71.67%. Two cut leaves are obtained yield 0.49%, moisture content 0.842%, specific gravity 0.921, refractive index 1.465, solubility in 70% alcohol 1: 3, cineol content 63.33. Cut eucalyptus oil leaves three obtained yield 0.39, water content 0.908, specific gravity 0.924, inex bias 1.465, solubility in 70% alcohol 1: 4, cineol content 68.33%. Treatment of leaf size significant effect on yield, solubility in 70% alcohol and not significant effect on specific gravity, refractive index, and cineol content.